Reactive transport modelling insights into CO2 migration through sub-vertical fluid flow structures. (July 2019) - Marín-Moreno, H.; Bull, Jonathan M.; Matter, Juerg M.; Sanderson, David J.; Roche, Ben J.
Highlights: CO2 -induced changes in chimney's porosity/permeability are minor at decadal scales. Seabed CO2 leakage via chimneys depends on the pre-existing hydrogeological state. We only predict leakage with chimney permeabilities >10 −14 m 2 and CO2 content >30%. Chimney permeabilities of 10 −14 m 2 result from fracture apertures >0.05 mm. Abstract: Sub-vertical geological structures that cut through the overburden, usually called chimneys or pipes, are common in sedimentary basins. Chimneys behave as conduits that hydraulically connect deep strata with the overburden and seabed. Hence, if stored CO2 migrates to a sufficiently high permeability chimney the risk of CO2 leakage at the seabed increases. Despite the possible negative effects these structures may have on the integrity of CO2 storage sites, little is known about (i) their effective permeability distribution, controlled by the combined role of fractures and matrix, and (ii) feedback mechanisms between porosity-permeability, CO2 reactivity and mineralogy within them. Reactive transport modelling is used to perform 2D axisymmetric radial simulations of geological systems containing chimneys. CO2 saturations of 10%, 30% and 50% are imposed on a cell located next to the symmetry axis at the base of the model. Under hydrostatic conditions, CO2 reaches the seabed, at 500 m above the injection point, in less than 100 yr using injected CO2 saturations at or above 30% and with overburden isotropic permeabilities and chimney vertical permeabilities above 10 −14 m 2 . Vertical fractures with apertures larger than 0.05 mm for volume fractions below 1% are sufficient to sustain such high vertical permeabilities in the chimney with a relatively high cap rock matrix permeability of 10 −16 m 2 . Over 100 yr of CO2 injection, changes in porosity and permeability due to mineral precipitation/dissolution are negligible. For this time scale, in systems containing chimneys sufficiently far away from the injection well, the risk of CO2 leakage at the seabed is primarily controlled by the pre-existing hydrogeological state of the system.